Effects of a staff-led multicomponent physical activity intervention on preschooler's fundamental motor skills and physical fitness: The ACTNOW cluster-randomized controlled trial - Elisabeth Straume Haugland; Ada Kristine Ofrim Nilsen; Kristoffer Buene Vabø; Caterina Pesce; John Bartholomew; Anthony David Okely; Hege Eikeland Tjomsland; Katrine Nyvoll Aadland; Eivind Aadland (BMC, 2024)
Abstract Background Fundamental motor skills (FMS) and physical fitness (FIT) play important roles in child development and provide a foundation for lifelong participation in physical activity (PA). Unfortunately, many children have suboptimal levels of PA, FMS, and FIT. The Active Learning Norwegian Preschool(er)s (ACTNOW) study investigated the effects of a staff-led PA intervention on FMS, FIT, and PA in 3-5-year-old children. Methods Preschools in Western Norway having ≥ six 3-4-year-old children were invited (n = 56). Of these, 46 agreed to participate and were cluster-randomized into an intervention (n = 23 preschools [381 children, 3.8 yrs., 55% boys]) or a control group (n = 23 [438, 3.7 yrs., 52% boys]). Intervention preschools participated in an 18-month PA intervention involving a 7-month staff professional development between 2019 and 2022, amounting to 50 h, including face-to-face seminars, webinars, and digital lectures. Primary outcomes in ACTNOW were cognition variables, whereas this study investigated effects on secondary outcomes. FMS was measured through 9 items covering locomotor, object control, and balance skills. FIT was assessed as motor fitness (4 × 10 shuttle-run test) and upper and lower muscular strength (handgrip and standing long jump). PA was measured with accelerometers (ActiGraph GT3X +). All measures took place at baseline, 7-, and 18-month follow-up. Effects were analysed using a repeated measures linear mixed model with child and preschool as random effects and with adjustment for baseline scores. Results Participants in the intervention preschools showed positive, significant effects for object control skills at 7 months (standardized effect size (ES) = 0.17) and locomotor skills at 18 months (ES = 0.21) relative to controls. A negative effect was found for handgrip strength (ES = -0.16) at 7 months. No effects were found for balance skills, standing long jump, or motor fitness. During preschool hours, sedentary time decreased (ES = -0.18), and light (ES = 0.14) and moderate-to-vigorous PA (ES = 0.16) increased at 7 months, whereas light PA decreased at 18 months (ES = -0.15), for intervention vs control. No effects were found for other intensities or full day PA. Conclusions The ACTNOW intervention improved some FMS outcomes and increased PA short-term. Further research is needed to investigate how to improve effectiveness of staff-led PA interventions and achieve sustainable improvements in children's PA, FMS, and FIT. Trial registration Clinicaltrials.gov, identifier NCT04048967 , registered August 7, 2019. Funding ACTNOW was supported by the Research Council of Norway (grant number 287903), the County Governor of Sogn og Fjordane, the Sparebanken Sogn og Fjordane Foundation, and the Western Norway University of Applied Sciences.